Ergonomic Panel Angles for Kitchen Appliances with Cooker Knobs - Minseok Son; Sehee An; Donghyun Beck (Applied Sciences)
Kitchen appliance control panels come in various designs, each with different parameter values. Of these design parameters, the panel angle is a key factor that impacts both usability and user preference. This study empirically investigates the effects of panel angles on the usability of knob panels in kitchen appliances. The research focused on identifying the optimal panel angles for visibility, physical comfort, and user preference. Six different panel angles (0°, 15°, 30°, 45°, 60°, and 90°) were tested through an experimental setup simulating a typical kitchen environment. Twenty participants, with experience in operating kitchen appliances, provided subjective ratings on the three usability factors using a 7-point Likert scale. The results demonstrated significant impacts of panel angle on all three measures, with angles between 45° and 60° showing the highest usability scores. The study highlights that the appropriate panel angle for knob panels should fall between 30° and 90°, with 45° to 60° being the optimal range. The results of this study could contribute to the ergonomic design of kitchen appliances, enhancing usability and minimizing human errors and response times during emergencies.